An integrative pan-cancer analysis of USP37 and functional validation in pancreatic cancer - Jiafei Chen; Jiafei Chen; Liang Lin; Dongxing Chen; Jingui Wang; Wuhan Zhou (Frontiers in Cell and Developmental Biology)
BackgroundUSP37, a versatile deubiquitinase, plays a pivotal role in numerous cellular functions. Although its involvement in cancer development is well-established, the comprehensive pan-cancer analysis of USP37 remains relatively uncharted.MethodsRNA sequencing data from both normal and cancerous tissues were retrieved from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases. Genomic alterations in USP37 across multiple cancer types were examined using cBioPortal. Protein-related information on USP37 was sourced from the Human Protein Atlas (HPA) and Protein-Protein Interaction (PPI) databases. Additionally, Western blotting was conducted to evaluate USP37 expression in clinical samples and pancreatic cancer cell lines. The prognostic relevance of USP37 across various cancers was analyzed using univariate Cox regression and Kaplan–Meier survival curves. Gene Set Enrichment Analysis (GSEA) was performed to identify cancer hallmarks associated with USP37. USP37 protein levels were quantified via immunoblotting, and in vitro and in vivo functional assays were employed to assess its role in the proliferation of pancreatic cancer cells.ResultsUSP37 was found to be aberrantly expressed in several tumor types, with significant association with poor prognosis in certain cancers, including pancreatic cancer. Its expression was also strongly correlated with immune regulators, tumor mutational burden (TMB), and microsatellite instability (MSI), highlighting its potential as a predictive marker for immunotherapy outcomes. Functional assays demonstrated that USP37 fosters proliferation, migration, and invasion in pancreatic cancer cells, further underscoring its role as an oncogene.ConclusionUSP37 holds promise as a biomarker and therapeutic target in clinical oncology, providing new insights into its function in cancer.